Technology-Assisted Language Learning Adaptive Systems: A Comprehensive Review - Parneet Kaur; Harish Kumar; Sakshi Kaushal (International Journal of Cognitive Computing in Engineering, 2023)
Technology-aided learning is one of the important aspects of cognitive computing where education is provided through the means of digital media. This paper presents a comprehensive review of trends and the development of technology-based adaptive language learning systems. It also strives to highlight challenges and opportunities in the field of Technology-Assisted Language Learning (TALL). Articles from various electronic databases and reputed journals in the related field have been reviewed from 2011to 2021 to get an insight into state-of-the-art adaptive systems for TALL. To analyze results, the authors have proposed three dimensions viz. spatial and temporal aspects, system and targeted learners’ characteristics, and adaptation provided. The findings of the review indicate that research in this field has been gaining popularity since 2015, especially in the Asian region. English is the most frequently investigated language in TALL systems which have been employed majorly for university students. The study also analyzes various methods and sources of adaptation provided in such systems. Challenges, opportunities, limitations, and implications of research in this direction have also been discussed. The study also proposes new ways and ideas that can be taken up and implemented by language educators and local governments to make the research in the field of TALL commercially feasible and penetrable to various levels of society.